Development of Efficient AAV2/DJ-Based Viral Vectors to Selectively Downregulate the Expression of Neuronal or Astrocytic Target Proteins in the Rat Central Nervous System - Jollé, Charlotte; Déglon, Nicole; Pythoud, Catherine; Bouzier-Sore, Anne-Karine; Pellerin, Luc (Frontiers in Molecular Neuroscience, 2019)
Viral vectors have become very popular to overexpress or downregulate proteins of interest in different cell types. They conveniently allow the precise targeting of well-defined tissue areas, which is particularly useful in complex organs like the brain. In theory, each vector should have its own cell specificity that can be obtained by using different strategies (e.g. using a cell-specific promoter). For the moment, there is few vectors that have been developed to alternatively target, using the same capsid, neurons and astrocytes in the central nervous system. There is even fewer examples of adeno-associated viral vectors able to efficiently transduce cells both in vitro and in vivo. The development of viral vectors allowing the cell-specific downregulation of a protein in cultured cells of the central nervous system as well as in vivo within a large brain area would be highly desirable to address several important questions in neurobiology. Here we report that the use of the AAV2/DJ viral vector associated to an hybrid CMV/chicken β-actin promoter (CBA) or to a modified form of the glial fibrillary acidic protein promoter (G1B3) allows a specific transduction of neurons or astrocytes in more than half of the barrel field within the rat somatosensory cortex. Moreover, the use of the miR30E-shRNA technology led to an efficient downregulation of two proteins of interest related to metabolism both in vitro and in vivo. Our results demonstrate that it is possible to downregulate the expression of different protein isoforms in a cell-specific manner using a common serotype. It is proposed that such an approach could be extended to other cell types and used to target several proteins of interest within the same brain area.